Unraveling Candidiasis: Pathogenic Mechanisms and the Spectrum of Infections - Asawari, Paryekar; Talreja, Shreya; Rohan, Barse; ., Jagtap Vijay (Asian Journal of Pharmaceutical Research and Development, 2025)
Worldwide, fungal infections—especially those brought on by Candida species like Candida albicanscause a considerable amount of illness and mortality, particularly in people with weakened immune systems. Through morphological changes, adhesion, invasion, biofilm formation, and the release of hydrolytic enzymes, Candida albicans demonstrates complicated pathogenicity. Its pathogenicity is increased by its capacity to change phenotypes and adjust to shifting environmental conditions. Drug-resistant strains such as Candida auris are becoming more and more common, which emphasizes the urgent need for efficient therapies and a better comprehension of the mechanisms behind fungal pathogenicity. Oral and vulvovaginal infections are among the many forms of candidiasis caused by Candida species, especially Candida albicans. Whereas vulvovaginal candidiasis affects the female reproductive system, oral candidiasis presents as thrush. Hormonal fluctuations, antibiotic usage, and immunosuppression are risk factors. Antifungal drugs are one kind of treatment; recurrence is frequent in some groups. Candida species, including Candida albicans, are responsible for a number of illnesses, including invasive candidiasis, gastrointestinal infections, and skin infections. Immunocompromised people are more susceptible to these infections, which can range from localized skin and gastrointestinal colonization to potentially fatal systemic infections. Antifungal drugs such as amphotericin B, azoles, and echinocandins are used in treatment.